2022
DOI: 10.3390/biomedicines10123204
|View full text |Cite
|
Sign up to set email alerts
|

More than Ninety Percent of the Light Energy Emitted by Near-Infrared Laser Therapy Devices Used to Treat Musculoskeletal Disorders Is Absorbed within the First Ten Millimeters of Biological Tissue

Abstract: There is increasing interest in the application of near-infrared (NIR) laser light for the treatment of various musculoskeletal disorders. The present study thoroughly examined the physical characteristics of laser beams from two different laser therapy devices that are commercially available for the treatment of musculoskeletal disorders. Then, these laser beams were used to measure the penetration depth in various biological tissues from different animal species. The key result of the present study was the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 44 publications
2
33
1
Order By: Relevance
“…The study conducted by [163] Overall, the study's findings support the potential advantages of multi-modal neurosupportive energy therapy as a complementary treatment for people with neurodegenerative diseases. To better understand the therapeutic potential of these interventions, Neuron Foundry Mach 8 needs to be completed and tested.…”
Section: B Comparative Analysis With Kaub and Schmitz: Different Appr...mentioning
confidence: 54%
See 1 more Smart Citation
“…The study conducted by [163] Overall, the study's findings support the potential advantages of multi-modal neurosupportive energy therapy as a complementary treatment for people with neurodegenerative diseases. To better understand the therapeutic potential of these interventions, Neuron Foundry Mach 8 needs to be completed and tested.…”
Section: B Comparative Analysis With Kaub and Schmitz: Different Appr...mentioning
confidence: 54%
“…The study conducted by [163] shares similarities with the Neuron Foundry Mach 8 concept in its focus on the therapeutic application of light, although there are notable differences in methodology and target outcomes. Both studies leverage light as a therapeutic tool, showcasing the versatility of light-based therapies in addressing various medical conditions, depending on the specific wavelengths and applications.…”
Section: Resultsmentioning
confidence: 99%
“…In the authors’ opinion, the reasons for the mixed research outcomes reported in the literature when small optic probes are employed is related to the issue of achieving radiant exposure (J/cm 2 ) adequate for targeting tissues over larger areas, particularly in the case of some sub-surface conditions, where the treatment area may extend to several cm 2 or more. Attenuation of the applied beam, in view of optical scatter in the red to NIR wavelength regions, reduces photon delivery at a depth of 5–10 mm to approximately 5–10% of the dose applied to the surface [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. To compensate for this energy loss, it is therefore necessary to increase the dose delivered to the surface by at least 10-fold in order to achieve the desired value at a depth of 10 mm [ 4 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation of the applied beam, in view of optical scatter in the red to NIR wavelength regions, reduces photon delivery at a depth of 5–10 mm to approximately 5–10% of the dose applied to the surface [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. To compensate for this energy loss, it is therefore necessary to increase the dose delivered to the surface by at least 10-fold in order to achieve the desired value at a depth of 10 mm [ 4 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation